ANALYSIS OF DISTINGUISHING POWER ON MATHEMATICS SUBJECT TEST QUESTIONS IN FOURTH GRADE OF SDN 136 PEKANBARU - Khumaira, Raissa; Ramadan, Rully Rachmawati; Khairunnisa, Sabrina; Jannah, Miftahul; Marhadi, Hendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
Power different question is ability question for show difference students who master material with students who have not in its entirety control material said. Analysis Power different question can help measure effectiveness question in differentiate ability students, improve quality assessment, and support development quality test. Research​ This aiming for analyze Power different question test mathematics at SDN 136 Pekanbaru so that it can determine question test that has Power differentiator positive to stay effectively used in assessment next. Method research used​ is approach quantitative with technique documentation data collection, in the form of sheet answer students on the test eye lesson mathematics in Fourth Grades of elementary school. Research results This show that: question test Mathematics in Fourth Grades at SDN 136 Pekanbaru in the year 2023/2024 academic year from a total of 25 questions as many as 9 questions (36%) are of poor quality Well, as many as 7 questions (28 %) were of sufficient quality and as many as 9 questions (36 %) were of good quality. Based on Power different question test Mathematics in class IV SDN 136 Pekanbaru 9 quality questions Good can used back on test next and 11 questions quality enough and less Good must revised moreover formerly If want to be used in the test next so that the quality Power different question own Power different positive and steady effective used.